Exposure and analysis of microparticles embedded in silica aerogel keystones using NF3‐mediated electron beam–induced etching and energy‐dispersive X‐ray spectroscopy. (29th April 2016) - Martin, Aiden A.; Lin, Ting; Toth, Milos; Westphal, Andrew J.; Vicenzi, Edward P.; Beeman, Jeffrey; Silver, Eric H.
Abstract: In 2006, NASA's Stardust spacecraft delivered to Earth dust particles collected from the coma of comet 81P/Wild 2, with the goal of furthering the understanding of solar system formation. Stardust cometary samples were collected in a low‐density, nanoporous silica aerogel making their study technically challenging. This article demonstrates the identification, exposure, and elemental composition analysis of particles analogous to those collected by NASA's Stardust mission using in‐situ SEM techniques. Backscattered electron imaging is shown by experimental observation and Monte Carlo simulation to be suitable for locating particles of a range of sizes relevant to Stardust (down to submicron diameters) embedded within silica aerogel. Selective removal of the silica aerogel encapsulating an embedded particle is performed by cryogenic NF3 ‐mediated electron beam–induced etching. The porous, low‐density nature of the aerogel results in an enhanced etch rate compared with solid material, making it an effective, nonmechanical method for the exposure of particles. After exposure, elemental composition of the particle was analyzed by energy‐dispersive X‐ray spectroscopy using a high spectral resolution microcalorimeter. Signals from fluorine contamination are shown to correspond to nonremoved silica aerogel and only in residual concentrations.